PERAN PERBANKAN SYARIAH DALAM MENINGKATKAN INKLUSI KEUANGAN DI INDONESIA - Putri Fitriyani; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
This study aimed to analyze the role of Islamic banks in promoting financial inclusion in Indonesia. Financial inclusion is a crucial process that provides formal financial access to the poor and low-income individuals, often referred to as the unbankable. The research employed a qualitative approach to gather in-depth insights into this topic. The qualitative data were analyzed using Strauss and Corbin’s grounded theory, which involves three major steps: open coding, axial coding, and selective coding. Through this methodology, the study highlighted the significant potential of Islamic banking in enhancing financial inclusion. The findings indicated a substantial increase in funding and financing activities from 2010 to 2014, demonstrating the growing impact of these banks on the financial landscape. Furthermore, the analysis of financial ratios revealed that the performance of Islamic banks is robust, reflecting sound financial condition. The research underscores that Islamic banks can effectively reach underserved populations, thus contributing to broader economic development and social equity in Indonesia. By offering Sharia-compliant products and services, these banks cater to the needs of those who may be hesitant to engage with conventional a banking systems. Overall, this study is emphasizes the importance of Islamic banks as key players in advancing financial inclusion, highlighting their ability to provide essential financial services to marginalized communities, ultimately fostering inclusive economic growth. This role is especially vital in a developing country like Indonesia, where access to financial resources can significantly change the lives of many individuals and families. since 2010-2014 and results of financial ratio analysis .